The comprehensiveness of inclusive junior high school principal performance - Miranda Batista, Dr. C. Yosvani Julio; Barrios Queipo, Dr. C. Enrique Aurelio; Castro Alvarez, Sandra (Transformación, 2021)
Objective: The paper aims at describing a pedagogic strategy to promote a comprehensive performance of junior high school principals.  Methods: The authors rely on theoretical methods to construct a conceptual framework for devising a strategy (scientific sources and documents reviewing). The strategy was assessed by experimental procedures.Results: The main finding is the description of a pedagogic strategy that promotes comprehensiveness in principals’ performance by relating leadership in professional pedagogic activity, sociopolitical requirements and technologies.Conclusion: Within inclusive scenario, educational institution principals need training for achieving a comprehensive performance. The devised strategy favors such comprehensiveness.
Keywords: leadership training; educational coordination; comprehensive schools; democratization of education